The revolution of Robert Kennedy : from power to protest after JFK - Bohrer, John R. (Bloomsbury Press, 2017)
On November 22, 1963, Bobby Kennedy received a phone call that altered his life forever. The president, his brother, had been shot. JFK would not survive. In The Revolution of Robert Kennedy, journalist John R. Bohrer focuses in intimate and revealing detail on Bobby Kennedy's life during the three years following JFK's assassination. Torn between mourning the past and plotting his future, Bobby was placed in a sudden competition with his political enemy, Lyndon Johnson, for control of the Democratic Party. No longer the president's closest advisor, Bobby struggled to find his place within the Johnson administration, eventually deciding to leave his cabinet post to run for the U.S. Senate and establish an independent identity. Those overlooked years of change, from hardline attorney general to champion of the common man, helped him develop the themes of his eventual presidential campaign. The Revolution of Robert Kennedy follows him on the journey from memorializing his brother's legacy to defining his own. John R. Bohrer's rich, insightful portrait of Robert Kennedy is biography at its best--inviting readers into the mind and heart of one of America's great leaders. -- Inside jacket flap.